Observations on the Armenian Higher Council Decisions (Orthoepy and Orthography) - AVETISYAN, YURI (Bulletin of Yerevan University B: Philology, 2021)
In the realm of orthoepy and orthography, there are issues that are subject to discussion and regulation, such as the use of quotation marks, the principles of abbreviation, etc. We believe, that to solve the problems mentioned above, we need new or revised resolutions as the living language is constantly evolving and changing and in order to abolish the parallel forms, the only way to perfect the literary language with the logic of living language is from time to time to turn to these problems with resolutions.
Keywords: regulation, shifts, norm of the literary language , orthoepy, spelling, stress, orthography, decision, specification